Specification and recognition of service trust behaviors - Hamdi Yahyaoui; Jumana El-Qurna; Mohamed Almulla (Kuwait Journal of Science)
We propose in this paper a new approach for the specification and recognition of service trust behaviors through the so-called trust patterns, which denote typical trust behaviors. The trust patterns are defined based on context free languages and modeled as pushdown automata. Furthermore, we provide a unified model to capture these patterns and prove the correctness of the proposed model. Finally, we conduct a comprehensive experimental study using Weka in which we test different classifiers on a dataset of trust sequences and provide a comparative study regarding the accuracy of these classifiers.